SYSTEM CONSOLIDATED SALARY EMPLOYEE IN. KAWASHIMA ENGEERING PLASTIC INDONESIA - Maria Renta; Aqwam Rosadi Kardian, SKom, MM Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2004)
Along with the advancement in information technology are now rapidly developing and propagating in different companies. Talking about the company can not be separated from the issue of salary employees, they can improve their performance at PT. Kawashima Engineering Plastic Indonesia. The problem for the payroll reporting system in data processing is not effective and efficient in this case the author tries to discuss the Report System Salaries of employees in PT. Kawashima Engineering Plastic Indonesia.